The capabilities of modern color proofing - Турчинова, Галина Ивановна; Васильева, Виктория Павловна (Technology audit and production reserves, 2013)
The subject of this work is the opportunities of modern color proofs. High print quality, speed, ease of use and reliability are very important for professional printing. The aim of this work is to determine the technological capabilities of inkjet printer EpsonStylusPhoto 2100 to provide an accurate simulation of color print. The advantage of color proofing is the ability of imitation of any printing process, ink usage, which imitate the colors of Pantone, including metallic inks, printing on papers of different types. Digital proofing is much cheaper than analog proofing. This fact attracts publishers nowadays. In this study, we evaluated the quality of color, with an inkjet printer EpsonStylusProEpsonStylusPhoto 2100. For the sake of clarity and a level playing field, we used several types of papers. The resulting prints were evaluated on criteria such as visual quality of printing, reproduction of text, reproduction of fine lines, the combination of colors, gradation properties, depth of black, the balance of "the gray", contrast and color range. Also, using a spectrophotometer the presence of prints metometry effects were analyzed. Furthermore, the results were evaluated and optimized for parameters of this printer.